Interactions between the haematopoietic stem cell and the myeloid microenvironment in aplastic anaemia - Novitzky, Nicolas (Division of Clinical Haematology, 2017)
In patients with aplastic anaemia that respond to immunosuppressive therapy, quantitative, morphological and functional haematologic derangement have been reported. To explain these findings, abnormalities in the marrow stroma or the stem cell have been postulated. To define the relative contribution of each of the latter, the integrity of the bone marrow from sixteen patients that responded to anti-lymphocyte globulin and high dose methyl prednisolone was compared to normal individuals. Bone marrow mononuclear cells were divided into two fractions. From the first, stroma was cultured in aMEM containing 12.5% of both horse and foetal calf serum and 10-5 M hydrocortisone at 37° C in 5% CO2 in 90% humidity. The medium was changed weekly. Upon confluence, these stromal layers were studied morphologically and with cytospin preparations stained with Sudan black, 0 red oil, alkaline and acid phosphatases. The remainder was monocyte and lymphocyte depleted, CD 34+ progenitors were selected with paramagnetic beads and the population morphologically and immunophenotypically defined. To determine the functional status, control or patient CD 34+ progenitors, were suspended for two hours on normal or aplastic stroma for adherence to take place. The non-adhesive fraction was decanted by standardised washing and cultured for fourteen days in the presence of PHA-conditioned medium in the CFU-gm assay. Strama-adherent progenitors were covered with 0.3% agar and cultured for five days. Aggregates with more than twenty cells were scored (CFU-bl). The remaining CD 34+ cells were cultured in the mixed colony assay with combinations of recombinant cytokines belonging to the G protein super-family and the tyrosine kinase group in dose response studies. Light density cells from patients with treated aplasia contained significantly fewer CD 34+ cells than those present in the control suspensions (mean 0.65%, SD 0.35% vs 1.62%, SD 1.4%; p= 0.002). Normal and aplastic stroma became confluent at three and four weeks. There was no difference on the morphology or the cytochemical stains between the two groups. Functionally, aplastic bone marrow stroma supported CFU-bl formation no differently from normal layers. However, CD 34+ precursors from the patients cultured on control stroma resulted in significantly fewer CFU-bl (p= 0.0002,) and CFU-gm (p= 0.0009). This work provides original evidence supporting the reduced clonogenicity of the corresponding populations of CFU-bl from patients with aplasia is unrelated to attachment to the stroma, but intrinsic to the CD 34+ cells. Moreover, this study shows for the first time that exposure of these progenitors to growth factors belonging to the G protein and tyrosine kinase receptor families have defective responses, correctable only at supra physiological concentrations, while effects on combinations containing c-kit ligand, appear preserved. Following immunosuppressive therapy, the bone marrow is repopulated by a hypoproliferative progenitor cell population which responds suboptimally to physiological cytokine stimulation. This suggests that abnormal interactions between receptors and their ligands or alterations in the signal transduction for cell division by the cytokines belonging to the G superfamily lead to suboptimal growth.